Directive Speech Act Employed In The English Translation Of The Nobel Al-Qur’an - Rugaiyah (CV. Inara, 2021)
The study aims at identifying (1) types of directive acts are employed in the English translation of the Noble Qur’an (2) the function of directive act are in an English translation of the Noble Al- Qur’an. This study employed a critical descriptive research to find the types of directives speech act and uncover the function of directive speech act. This research data is in the form of speech in AlQur’an containing the act of directive speech. Data collection is done by careful and critical reading techniques (critical reading) to obtain speeches that contain the meaning of directives both command and prohibition, either delivered directly or indirectly. The collected data is then selected and classified based on the type of speech nature (commands, prohibitions) and the way it is delivered (direct vs. indirect). The next step is to analyse the data found from each verse in the Al-Quran. This analysis is done with a content analysis approach to uncover the functions of speechless directives found in the nature of the Al-Quran. The use of indirect speech in the Al-Qur'an is intended to glorify speech partners with polite language. Indirect speech is one indicator of language modesty because it is considered more polite than direct speech. Indirect speech in the AlQur'an indicates that the Al-Qur'an is a holy book with a very polite language, the most beautiful language that cannot be matched by anyone from the ancients until the end of time. Based on the data analysis it is found that most of verse uttered by Allah SWT are in the form of command.